Fitrah and the Role of Women According to Said Nursi - Jarman Arroisi; Nailul Izzah; Muhammad Nur Khalim (al-Afkar, Journal For Islamic Studies, 2025)
Islam privileges the position of women where previously they were in a low position, even in pre-Islamic times the birth of a woman was a very shameful disgrace. However, in reality, from the womb of a woman, a generation will emerge that will bring about changes in the social order of society and also civilization. Said Nursi through Risale Nur has given special notes to women, this research uses library research methods with the main source being the Risale Murshid Akhwat wa al-akhirah. Ibnu Katsir, al-Maraghi which is managed using descriptive analysis methods. The results of the research in this paper show the conclusion that fitrah is the basis for recognizing the oneness of God. Islam divides the dimensions of nature into 3, namely; Biological, Spiritual and Psychological, in the role of women's nature, it concludes that women's nature is to love and defend their children, this is God's gift given to women, Said Nursi likens women's nature to being a brave mother hen. fighting dogs to defend her children. The characteristics of a true woman in Nursi's view are having the qualities of Syafaqah, protecting their private parts, akhlaqul karimah, and being the first school for their children.